From Design to Research: Upper Limb Prosthetic Research and Development in Canada, 1960-2000 - Foord, David; Kyberd, Peter (Scientia Canadensis, 2015)
This paper examines the history of the research and development (R&D) of myoelectric upper limb prosthesis in Canada from 1960 to 2000. It focuses on two of the prosthetic research and training units (PRTUs) that were created and funded by the federal government as a result of the Thalidomide tragedy: the Rehabilitation Centre at the Ontario Crippled Children’s Centre (OCCC) and successor organizations, and the University of New Brunswick’s (UNB) Institute of Biomedical Engineering (the Institute or IBME). Both developed commercial systems for myoelectrically controlled arms and hands. We argue that, in contrast to the common view that research in universities and public research institutions has increasingly moved away from basic problems and to product development and commercialization over the period, research in this field has moved in the opposite direction. We explore these cases in detail and examine the forces at work in this change from a design-oriented approach to one that became research intensive.